(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2021)
A hypothetical learning trajectory line is described for the assimilation and fixation of the concept of height of a triangle for its treatment in pre-university. The theoretical and methodological basis is based on the processes of assimilation, learning trajectories, problem solving and the use of GeoGebra software. This work provides a didactic proposal aimed at the teacher, different from the classic presentation for the treatment of the concept of height, highlighting that the use of the software favors the processes of assimilation of this concept through the dynamic-visual activity, use of the geometric and numerical resource that this technological tool makes possible.